Stephanie B. Anderson: Crafting EU Security Policy: In Pursuit of a European Identity. (Czech Journal of International Relations, 2010)
Stephanie B. Anderson: Crafting EU Security Policy: In Pursuit of a European Identity. 1st ed. Boulder: Lynne Rienner Publishers, 2008, 235 stran, ISBN 978-1-58826-582-1 (signatura knihovny ÚMV 55 588).